66 Comparison Between Transradial and Femoral Approach for Rotational Atherectomy in Contemporary Practice- A Large Single Centre Experience. (31st May 2014) - Garner, Daniel; Balakrishnan Nair, Satheesh; Patel, Billal; Beaumont, Andy; Shaw, Matthew; Perry, Raph; Andron, Mohammed
Abstract : Introduction: Transradial access is often avoided for rotablation atherectomy (RA) because of concern over limitations of guiding catheter (GC) size. Radial operators have used sheathless GC to overcome this. However, coronary dissection has been reported more often with sheathless GC. Furthermore, in contemporary PCI, larger size burr is rarely required. Also, It is known that access site bleeding complications are more common with femoral procedures. Finally, long-term clinical outcomes of patients undergoing RA with either of these approaches are not well known in the current era of PCI. Aim: The aim of this study was to compare the procedural success rates, in-hospital and long-term clinical outcomes in patients undergoing RA via radial and femoral routes. Methods: We retrospectively studied consecutive patients who underwent RA from April 2008 to October 2013 in a high volume tertiary cardiac centre. Procedure related bleeding was graded as per the Bleeding Academic Research Consortium (BARC) definition. MACE was defined as composite endpoint of death, MI, stent thrombosis and target lesion/vessel revascularisation. Results: A total of 254 patients underwent RA (72% radial and 28% femoral) procedure during the study period. The median follow-up period was 28 months (IQR 29 months). The baseline clinical and procedural characteristics are shown in Tables 1 and 2 respectively. Significantly, smaller size GC were used in the radial compared with the femoral group (6.4 ± 0.5 vs 6.8 ± 0.7, p = 0.00). In-hospital complications were twice more common in femoral than in radial RA (18.9 vs 9.0%, p = 0.03). Access site complications were almost 3 times higher in the femoral group (16.2 vs 6.1%, p = 0.02). There was no major bleeding (BARC score >2) in radial group compared to 4.1% in femoral patients (p = 0.002).A significantly higher proportion of elective PCI patients were discharged on the same day in the radial approach (79.2% vs 53.8%, p = 0.001). There was no significant difference between radial and femoral approaches in the in-hospital and long-term MACE events (2.2 vs 0.0%, p = 0.20 and 17.8 vs 12.2%, p = 0.27 respectively). Conclusions: In this large real world study population, we have shown that it is feasible to perform PCI with RA via radial approach with very high success rates, lower access site complications and similar long-term outcomes compared to femoral procedure. A significantly higher proportion of patients in the radial group were discharged on the same day with potential cost savings.